In Vitro Fermentability and Methane Production of Complete Feeds as Affected by Supplementation of Tree Leaves - Deuri, Pompi; Wadhwa, M. (Indian Journal of Animal Nutrition, 2018)
The study was taken up to assess the effect of supplementing tree leaves of Eucalyptus globules (safeda), Psidium guajava (guava) and Phoenix dactylifera (khajur) @ 1% on DM basis either individually or in combination on the in vitro fermentability and methane production potential of complete feed. Supplementation of diet with leaves of safeda, guava and khajur decreased net gas production (NGP) by 9.3, 7.6, 5.6%, respectively while the partition factor (PF) increased in comparison to unsupplemented diet. Thesupplementation of diet with tree leaves individually or in combination depressed the total and individual volatile fatty acids with mild increase in A: P ratio. The methane production was the lowest (P